Stumbling upon Palatogingival Groove: A Case Report - Thapa, Sujan; Gautam, Vanita; Shubham, Snigdha; Nepal, Manisha; Shrestha, Kriti (Journal of Universal College of Medical Sciences, 2021)
Palatogingival grooves (PGG) are developmental malformations infamous for precipitating endodontic-periodontal lesions. Pertaining to their discreet occurrence, variation in groove depth and funnel like shape, adherence of plaque and calculus is apparent thereby jeopardizing the periodontium and pulp. A case of palatogingival groove in maxillary left lateral incisor was diagnosed and managed with endodontic treatment followed by open flap debridement to seal the groove with biodentine and fill the defect with bone graft. On follow up, the periapical lesion and the periodontal pocket were successfully resolved.